Não-preferência para alimentação de traça-das-crucíferas por genótipos de couve-flor - Boica Junior, A.L.; Chagas Filho, N.R. (My University, 2009)
The feeding nonpreference of Plutella xylostella (L.) larvae was tested in regard to the cauliflower genotypes Barcelona, Verona, Piracicaba Precoce, Sharon, Silver Streak (hybrids) and Teresopolis Gigante (cultivar). Choice and no-choice tests were carried out at the laboratories of the Departamento de Fitossanidade, FCAV/UNESP, Jaboticabal, state of São Paulo, Brazil, to study attractiveness and dry mass consumption by 1st-instar (just hatched) and 4th-instar larvae for 24 hours. No significant difference was found for attractiveness in choice and no-choice tests, for both 1st-and 4th-instar larvae. The consumption of dry mass in both tests, with 1st-and 4th-instar larvae, showed a significant difference between genotypes only for 1st-instar larvae, the hybrid Silver Streak being the most consumed (3.72 mg) by P. xylostella larvae. The cauliflower genotypes tested presented no variation in attractiveness for 1st-instar (just hatched) and 4th-instar larvae and did not present nonpreference feeding resistance for P. xylostella larvae.
Feeding nonpreference of diamondback in cauliflower genotypes.